Polyphasic characterization of an ecologically differentiated novel cyanobacterium: Ammassolinea thermalis sp. nov. (Oscillatoriaceae, Oscillatoriales) isolated from a tropical hot spring in Malaysian Borneo - Ong, Yin Sing; Teng, Sing Tung; Abdullah, Nursyahida; Jamil, Nur Izzahalin; Wong, Olwena Rong Ying; Hii, Kieng Soon; Leaw, Chui Pin; Lim, Po Teen (Phytotaxa, 2026)
In this study, a novel cyanobacterium, Ammassolinea thermalis sp. nov., was isolated from a hot spring pool in Sarawak, Malaysia. The novel species was characterized using a polyphasic approach combining morphological observations and molecular phylogenetic analyses, and its ecological significance was evaluated. Morphologically, the trichomes form heap-like colonies composed of straight to slightly bent filaments, consistent with the genus Ammassolinea. Ammassolinea thermalis differs from A. attenuata by the occasional presence of capitate apical cells, slight cell and crosswall bulging, and rarely attenuated trichomes. Phylogenetic analyses based on the 16S rRNA gene placed the strains within the genus Ammassolinea and supported its separation from A. attenuata, although the genetic similarity was relatively high. Phylogenetic analyses of the 16S–23S ITS region and secondary structure comparisons revealed only minor differences, particularly within the V2 helix. However, the polyphasic approach which integrating morphological, molecular, and ecological evidence, supports the recognition of Ammassolinea thermalis as a novel species associated with geothermal habitats.